A little corner of freedom Russian nature protection from Stalin to Gorbachëv - Weiner, Douglas R. 1951- (Univ. of California Press, 1999)
A Little Corner of Freedom sheds new light on Soviet politics, revealing how a Russian nationalist movement used the protective umbra of environmentalism to become a cultural and political force, and how ordinary citizens used it to launch the first mass protests at the dawn of glasnost. It shows how activists were able to establish personal ties with local, provincial, and republic-level politicians who came to regard the movement and the nature reserves it promoted as a source of local pride.